De “uma teoria da Justiça” ao “direito dos povos”: uma concepção universalizável e igualitária de justiça e liberdade - Feldens, Guilherme de Oliveira (Universidade do Vale do Rio do Sinos, 2009)
John Rawls’s A Theory of Justice has reoriented western philosophic thought, starting a new period of reflection on justice. Designed so as to offer ‘one’ theory, this work does not present a dogmatic purpose; however, it does propose principles of justice, resulting from a hypothetical original agreement, to constitute what it calls ‘justice as fairness’, characterized by the foundation of the rules of ‘fair’ in the institutions. Therefore, the main theme of this theory are ‘the principles of justice’, and their application to society’s basic structure. Through the ‘veil of ignorance’ imposed to men in their ‘original position’, Rawls makes the design of such principles the result of a rational common sense among individuals, trying to achieve a moral ideal that works as an alternative for the utilitarian doctrine and as the basis for a fair democratic society. Rawls’s second most important work, Political Liberalism (1993) attempts to refute criticism addressing the presentation of his theory of justice as
Keywords: democracia; eqüidade; liberdade; pluralismo; justiça; democracy; fairness; freedom; pluralism; justice; Ciências Humanas